PENGARUH KEADILAN, KECURANGAN TEKNOLOGI, DISKIRIMINASI DAN NILAI SOSIAL TERHADAP PERSEPSI WAJIB PAJAK MENGENAI ETIKA PENGGELAPAN PAJAK (TAX EVASION) - Veronika, Mulur; Saleh, Muhammad (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
Taxes are the most important element in sustaining the budget in the form of state revenues. Running and realizing a national development plan, the government needs substantial funds to make it happen. But in reality there are many taxpayers who violate their tax obligations by carrying out tax evasion. This study aims to analyze the influence of justice, technology fraud, discrimination and social values on the perceptions of taxpayers regarding the ethics of tax evasion. The population of this study is taxpayers registered at KPP Pratama Banda Aceh. The sample in this study was determined based on the convenience sampling method, the data was collected by dividing 150 questionnaires. The method of research analysis used is multiple linear regression. The data uses the SPSS version 22 program. Based on the results and conclusions, the research shows that fairness, technology fraud, discrimination and social values have a positive and significant effect on the perception of taxpayers regarding the ethics of tax evasion. Overall, all four variables simultaneously influence tax evasion. Future studies are expected to be able to use other variables beyond this research model to enrich science, especially in the field of tax.